E. coli bacteremia in comparison to K. pneumoniae bacteremia: influence of pathogen species and ESBL production on 7-day mortality. Issue 1 (December 2016) - Leistner, R.; Bloch, A.; Gastmeier, P.; Schwab, F.
Abstract In a previous study, we demonstrated prolonged length of hospital stay in cases of extended-spectrum beta-lactamase (ESBL)-positiveK. pneumoniae bacteremia compared to bacteremia cases due toE. coli (ESBL-positive and –negative) and ESBL-negativeK. pneumoniae . The overall mortality was significantly higher in bacteremia cases resulting from ESBL-positive pathogens but also inK. pneumoniae cases disregarding ESBL-production. In order to examine whether pathogen species rather than multidrug resistance might affect mortality risk, we reanalyzed our dataset that includes 1.851 cases of bacteremia.